Keyboarding and formatting essentials - VanHuss, Susie H. (Thomson/South-Western, 2005)
Master basic document formatting and keyboarding with KEYBOARDING AND FORMATTING ESSENTIALS, LESSIONS 1-60! This easy-to-use keyboarding text teaches you the alphabetic keyboard, document formatting, and word processing skills using MS Word 2002 or Word 2003. Improve your proofreading skills as you go and use the skillbuilders to enhance your keyboard mastery!